The 3x3x3 diet for the management of diabetes and obesity in resource constrained settings - Sanjay Kalra; Leepica Kapoor; Nitin Kapoor (Journal of the Pakistan Medical Association, 2022)
In times when diseases like diabetes and obesity have attained pandemic proportions, it is essential to introduce lifestyle changes in early stages to prevent progression of these disorders. In health care systems with heavy patient load, time management is of utmost importance. In this communication, we share a simple 3x3x3 rubric based dietary prescription, which is easy to teach, and easy to grasp. It covers the most important dietary principles that are advocated in various evidence based clinical practice guidelines. Keywords: Diabesity, diabetes, obesity, lifestyle management, dietary advice, patient centered management, south Asian phenotype. Continue...